Ultrasound Assisted a Peroxisome Proliferator-Activated Receptor (PPAR)γ Agonist-Loaded Nanoparticle-Microbubble Complex to Attenuate Renal Interstitial Fibrosis - Wei S (Dove Medical Press, 2020)
Shuping Wei,1 Chaoli Xu,2 Yidan Zhang,1 Zhongqing Shi,3 Min Wu,1 Bin Yang2 1Department of Ultrasound, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, Jiangsu, People’s Republic of China; 2Department of Ultrasound, Jinling Hospital, Medical School of Nanjing University, Nanjing, Jiangsu, People’s Republic of China; 3Department of Cardiac Function, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Bin YangDepartment of Ultrasound, Jinling Hospital, Medical School of Nanjing University, 305 Zhongshan East Road, Nanjing, Jiangsu 210002, People’s Republic of ChinaTel +86-025-80861314Email yangbin12yx@163.comMin WuDepartment of Ultrasound, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, 321 Zhongshan Road, Nanjing, Jiangsu 210009, People’s Republic of ChinaTel +86-025-83304616Email wuminguyi@163.comObjective: To investigate the antifibrotic effect of the combination of a PPARγ agonist-loaded nanoparticle-microbubble complex with ultrasound (US) exposure on renal interstitial fibrosis (RIF).Materials and Methods: Polylactide-co-glycolide (PLGA) nanoparticles were used to load PPARγ agonist (rosiglitazone, RSG) and prepare PLGA-RSG nanoparticles (PLNPs-RSG); then, a novel complex between PLNPs-RSG and SonoVue microbubbles (MBs) (PLNPs-RSG-MBs) was prepared. The size distribution, zeta potentials, RSG-loading capacity and entrapment efficiency were measured, and the release of RSG was assessed using a UV-vis spectrophotometer. The in vitro cytotoxicity and in vivo systemic toxicity assays were performed. The cellular uptake assessment was performed using a confocal laser scanning microscope (CLSM). The in vivo biodistribution assessment was performed using fluorescence imaging with a near-infrared (NIR) imaging system. Furthermore, this complex was administered to a unilateral ureteral obstruction (UUO) rat model with the assistance of US exposure to investigate the antifibrotic effect.Results: This PLNPs-RSG-MBs complex had a size of 2199.5± 988.1 nm and a drug-loading efficiency of 28.5%. In vitro cytotoxicity and in vivo systemic toxicity assays indicated that the PLNPs-RSG-MBs complex displayed excellent biocompatibility. In addition, the complex showed high cellular uptake efficiency in vitro and kidney-targeting ability in vivo. In a UUO rat model, the combination of the PLNPs-RSG-MBs complex with US exposure significantly reduced collagen deposition and successfully attenuated renal fibrosis.Conclusion: The combination of the PLNPs-RSG-MBs complex with US exposure may be a promising approach for the treatment of RIF.Keywords: ultrasound, nanoparticles, microbubbles, peroxisome proliferator-activated receptor, renal interstitial fibrosis